Growth and Production of Long Bean (Vigna Sinensis L) Plants Against Various Doses of Chicken Cage Fertilizer - Wa Ode Anti; La Ode Lambela; Abdul Rahim Rahim; Muhammad ifa (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
Growth and Production of Long Bean (Vigna Sinensis L.) Plants Against Providing Various Doses of Chicken Cage Fertilizer This study aims to: (a) determine the effect of chicken manure, and (b) determine the dose of chicken manure that gives the best effect on the growth and production of string beans (Vignasinensis L.). The research was conducted in January-March 2020, located in Lamorende Village, Tongkuno District, Muna Regency. The study was compiled based on a randomized block design (RBD) with one factor, which consisted of four (4) treatment levels, namely A0 = without chicken manure (control), A1 = chicken manure with a dose of 10 tons ha-1 or 2.4 kg plot-1, A2 = Chicken manure with a dose of 20 tons ha-1 or 4.8 kg plot-1 and A3 = chicken manure with a dose of 30 tons ha-1 or 7.2 kg plot-1. The four treatments were arranged into three groups with 12 experimental units. Observation data from each parameter were analyzed by Analysis of Variance (ANOVA). Furthermore, to test the hypothesis using the F test at the 95% confidence level. The results showed that the dose of chicken manure had a very significant effect on plant height, number of leaves, number of pods per plant, pod weight per plant, and long bean crop production. Treatment of chicken manure with a dose of 30 tonnes ha-1 gave the best growth and production in long bean plants with average productivity of 11.72 t ha-1.